Methods for Developing the Lexical and Grammatical Competences of Future English Language Teachers - Nasriddinova M. Sh. (Scientific Trends, 2025)
The article is devoted to the stages and levels of forming lexical competence among future teachers of English. It examines modern methodological approaches, digital tools and didactic technologies used in teaching vocabulary. Special attention is given to the practical value of a systematic and integrated approach that ensures the development of professionally oriented lexical training of teachers.
Keywords: Lexical competence, teacher training, future English teachers, teaching methods, digital technologies, levels of lexical competence.